2022
DOI: 10.3393/ac.2020.00745.0106
|View full text |Cite
|
Sign up to set email alerts
|

McKittrick-Wheelock Syndrome: A Case Series

Abstract: McKittrick-Wheelock syndrome is a rare and life-threatening disease characterized by the triad of (1) chronic mucous diarrhea, (2) renal function impairment with hydroelectrolyte imbalance, and (3) a giant colorectal tumor. Often, the tumor is a rectal adenoma. With the mortality being certain, if left untreated, it is important to raise awareness on the presentation, diagnosis, and management of this disease entity. Here, we presented 3 cases of McKittrick-Wheelock syndrome that were successfully managed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…In our reported case, the patient was also admitted to the hospital due to electrolyte imbalance. However, there are referred cases in the literature with an atypical presentation of MWS at the emergency department with rectal prolapse, dermatomyositis, or with encephalopathy due to severe hyponatremia [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our reported case, the patient was also admitted to the hospital due to electrolyte imbalance. However, there are referred cases in the literature with an atypical presentation of MWS at the emergency department with rectal prolapse, dermatomyositis, or with encephalopathy due to severe hyponatremia [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently published studies have shown an increase in the usage of minimally invasive procedures such as transanal endoscopic microsurgery, transanal minimally invasive surgery, endoscopic mucosal resection, and endoscopic submucosal dissection [ 21 , 22 ]. However, some authors noticed that the risk of recurrence is greater after minimally invasive operations [ 4 , 9 , 18 ]. Endoscopic techniques may be technically challenging due to the large size of the tumor in MWS patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AM would therefore have been responsible in our patient for an equivalent of the electrolyte depletion syndrome (Mckittrick-Wheelock syndrome). This latter is a rare and life-threatening disease characterized by the triad of (1) chronic mucous diarrhea, (2) renal function impairment with hydroelectrolyte imbalance, and (3) a giant colorectal tumor ( Villanueva et al, 2022 ). The mechanism behind severe electrolyte and body fluid depletion in Mckittrick-Wheelock syndrome is suggested to involve cyclic adenosine monophosphate (AMP) and prostaglandin E2 acting as mediators, which increase the loss of fluid and electrolytes from the plasma to the intestinal lumen ( Steven et al, 1981 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such a pathology is potentially lethal, so it is of paramount importance to have greater knowledge about the clinic, diagnosis and therapy. 31 In 1941, for the first time, an acute kidney injury caused by secretory diarrhea arising from a colorectal villous adenoma associated with an exacerbated decrease in electrolytes was described in a case report, which was called "pre-renal uremia due to rectal papilloma". Only in 1954 was this syndrome titled by the eponym "McKittrick and Wheelock".…”
Section: Introductionmentioning
confidence: 99%